Sequence diversity of dengue virus type 2 in brain and thymus of infected interferon receptor ko mice: implications for dengue virulence. Issue 1 (December 2016) - Dhole, Priya; Nakayama, Emi; Saito, Akatsuki; Limkittikul, Kriengsak; Phanthanawiboon, Supranee; Shioda, Tatsuo; Kurosu, Takeshi
Abstract Background We previously reported that a clinical isolate of dengue virus (DENV) is capable of causing acute-phase systemic infection in mice harboring knockouts of the genes encoding type-I and -II interferon IFN receptors (IFN-α/β/γR KO mice); in contrast, other virulent DENV isolates exhibited slow disease progression in this mice, yielding lethal infection around 20 days post-infection (p.i.). In the present study, we sought to clarify the dynamics of slow disease progression by examining disease progression of a type-2 DENV clinical isolate (DV2P04/08) in mice. Methods The tissue distributions of DV2P04/08 in several organs of infeted mice were examined at different time points. Whole genome viral sequences from organs were determined. Results At day 6 p.i., high levels of viral RNA (vRNA) were detected in non-neuronal organs (including peritoneal exudate cells (PECs), spleen, kidney, liver, lung, and bone marrow) but not in brain. By day 14 p.i, vRNA levels subsequently decreased in most organs, with the exception of thymus and brain. Sequence analysis of the whole genome of the original P04/08 and those of viruses recovered from mouse brain and thymus demonstrated the presence of both synonymous and non-synonymous mutations. Individual mice showed different virus populations in the brain. The vRNA sequence derived from brain of one mouse was nearly identical to the original DV2P04/08 inoculum, suggesting that there was no need for adaptation of DV2P04/08 for growth in the brain. However, quasispecies (that is, mixed populations, detected as apparent nucleotide mixtures during sequencing) were observed in the thymus of another mouse, and interestingly only mutant population invaded the brain at a late stage of infection. Conclusions These results suggested that the mouse nearly succeeded in eliminating virus from non-neuronal organs but failed to do so from brain. Although the cause of death by DV2P04/08 infection is likely to be the result of virus invasion to brain, its processes to the death are different in individual mice. This study will provide a new insight into disease progression of DENV in mice.